Hubungan Gaya Hidup dan Motivasi dengan Perilaku Konsumtif pada Siswi SMA Al-Azhar Medan - Dewi Afriantie; Lahmuddin Lubis; Nur’aini Nur’aini (Universitas Medan Area, 2023)
This study aims to analyze the relationship between lifestyle and motivation with consumptive behavior among Al-Azhar High School students in Medan. This type of research is a quantitative study with a correlational approach with a sample of 128 Al-Azhar high school students obtained through screening. The research sample uses a total sampling technique. Measuring instruments used in this study are data collection techniques obtained through lifestyle scales, motivational scales and consumer behavior scales. Data analysis techniques used multiple regression analysis techniques with  = 0.05. The results of data analysis in this study indicate that there is a positive and significant relationship between lifestyle with consumptive behavior with p-value = 0,000, correlation coefficient rx1y = 0.780 and with determination r2 = 0.609 (60.9%). There is a positive and significant relationship between motivation with consumptive behavior with p-value 0,000, correlation rx2y = 0.734 and with determination r2 = 0.538 (53.8%). There is a positive and significant relationship between lifestyle and motivation with consumptive behavior with a p-value of 0,000, a correlation of rx1x2y = 0.857 and with a determination of r2 = 0.735 (73.5%). Thus it can be concluded that the higher the lifestyle and motivation, the higher the consumptive behavior. The suggestion in this research is that schools can create an atmosphere that can control the culture of consumptive behavior by doing charitable behavior such as sharing and saving.